Implementasi Strategi Manajemen Talenta untuk Retensi Tenaga Medis Spesialis di Rumah Sakit Daerah Melalui Insentif dan Pengembangan Karier - Putu Dewi Antari; Kurnia Datu Kanoena Lethe; Purwadhi Purwadhi; Yani Restiani Widjaja (Lembaga Pengembangan Kinerja Dosen, 2026)
Limited availability and high turnover of medical specialists remain major challenges for regional hospitals in Indonesia, affecting the quality and continuity of health services. This study aims to analyze the role of talent management through incentives and career development in improving the retention of medical specialists in regional hospitals. The research employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature searches were conducted across Scopus, PubMed, Google Scholar, and Sinta databases, covering publications from 2015 to 2025. A total of 52 articles that met the inclusion criteria were thematically analyzed. The findings indicate that integrated talent management practices, including strategic workforce planning, fair financial and non-financial incentives, and sustainable career development programs, have a significant impact on enhancing motivation, job satisfaction, and loyalty among medical specialists. In conclusion, effective retention strategies require synergy between talent management, competitive incentive systems, and continuous career development to ensure service quality and organizational sustainability in regional hospitals.